Probing mitochondrial peroxynitrite biogenesis by a N-morpholinoarylimine-based iridium(III) complex in drug-induced liver cells - Lingtan Kong; Ling Wang; Zixi Zhang; Liuqi Ye; Daniel Shiu-Hin Chan; Chun-Yuen Wong; Jing Wang; Chung-Hang Leung; Wanhe Wang (Redox Biology)
Peroxynitrite (ONOO−), a strong oxidizing agent, has an important function in the pathogenesis of various diseases, including cardiovascular, inflammatory and neurodegenerative diseases. Specifically, mitochondrial ONOO− exacerbates liver injury by driving oxidative/nitrative stress and mitochondrial dysfunction, ultimately triggering dual apoptotic-necrotic hepatocyte death pathways. ONOO− and its functions have been widely studied by fluorescence imaging probes, owing to their strong sensitivity, non-invasiveness, and real-time ability. However, existing probes are heavily constrained by interference from other reactive species. Herein, we describe a luminescent iridium(III) complex (1) with an N-morpholinoarylimine moiety as the recognition site for ONOO− for imaging mitochondrial ONOO−. The probe shows high luminescence response to ONOO− in aqueous buffer, with a luminescence enhancement of 27-fold at 100 μM ONOO− and a limit of detection (LOD) of 0.65 μM, as well as high selectivity over other reactive species. Furthermore, the probe can sense both exogenous and endogenous mitochondrial ONOO−. Further experiments demonstrated it could visualize exogenous ONOO− in 3D multicellular tumor spheroids (MCTSs) and unmask endogenous ONOO− production through an NADPH oxidase 4 (NOX-4)-mediated pathway in drug-induced liver cells. This work demonstrates the potential of this strategy for developing imaging tools for probing the pathological roles of subcellar ONOO− and diagnosing liver injury in the clinic.